Ultrastructural anatomy of nodes of Ranvier in the peripheral nervous system as revealed by STED microscopy - D'Este, Elisa; Hell, Stefan (Proceedings of the National Academy of Sciences of the United States of America, 2017)
We used stimulated emission depletion (STED) superresolution microscopy to analyze the nanoscale organization of 12 glial and axonal proteins at the nodes of Ranvier of teased sciatic nerve fibers. Cytoskeletal proteins of the axon (betaIV spectrin, ankyrin G) exhibit a high degree of one-dimensional longitudinal order at nodal gaps. In contrast, axonal and glial nodal adhesion molecules [neurofascin-186, neuron glial-related cell adhesion molecule (NrCAM)] can arrange in a more complex, 2D hexagonal-like lattice but still feature a ∼190-nm periodicity. Such a lattice-like organization is also found for glial actin. Sodium and potassium channels exhibit a one-dimensional periodicity, with the Nav channels appearing to have a lower degree of organization. At paranodes, both axonal proteins (betaII spectrin, Caspr) and glial proteins (neurofascin-155, ankyrin B) form periodic quasi-one-dimensional arrangements, with a high degree of interdependence between the position of the axonal and the glial proteins. The results indicate the presence of mechanisms that finely align the cytoskeleton of the axon with the one of the Schwann cells, both at paranodal junctions (with myelin loops) and at nodal gaps (with microvilli). Taken together, our observations reveal the importance of the lateral organization of proteins at the nodes of Ranvier and pave the way for deeper investigations of the molecular ultrastructural mechanisms involved in action potential propagation, the formation of the nodes, axon-glia interactions, and demyelination diseases.
Published ahead of print December 21, 2016
Gesehen am 25.10.2018